Workshop on Chaos in Brain? : NIC, Forschungszentrum Jülich and Dept. of Epileptology, University of Bonn, Germany, March 10-12, 1999 - Lehnertz, K. (Klaus) (World Scientific, 2000)
There has been a heated debate about whether chaos theory can be applied to the dynamics of the human brain. While it is obvious that nonlinear mechanisms are crucial in neural systems, there has been strong criticism of attempts to identify at strange attractors in brain signals and to measure their fractal dimensions, Lyapunov exponents, etc. Conventional methods analyzing brain dynamics are largely based on linear models and on Fourier spectra. Regardless of the existence of strange attractors in brain activity, the neurosciences should benefit greatly from alternative methods that have been developed in recent years for the analysis of nonlinear and chaotic behavior.